Proving the Resurrection in the Holy Quran By applying indirect logical reasoning, measurement and representation - Al-Khatib, Sharif; Hassouna, Omar (Jordan Journal of Islamic Studies, 2023)
This research tackles the issues of providing the resurrection according to two ways: the indirect inference: analogy, and comparison of the Holy Quran’s verses. In order to demonstrate the importance of logical mental reasoning in providing believes issues. Especially, those who don’t believe in the text at all. Besides, the paper inferences these evidences by providing examples from the Holy Quran’s texts only. The research concludes that analogy and comparison lead to certainty by indicating the belief’s evidence in general. Also it especially confirms the resurrection issues because it is our concern here.